Cooperative Integrated Reading and Composition (CIRC) Model on Students' Social Literacy - Fatmawati; Latifa Anisa; Fauzi; Abdi Hary; Yusrizal (Global Action and Education for Society, 2025)
This research was carried out to clearly determine the influence of the Cooperative Integrated Reading and Composition (CIRC) learning model on students' social literacy. This research was conducted at SDS IT DELISHA in class IV which was carried out on two experimental and control groups whose samples were from classes IV-A and IV -B. This study uses a quantitative approach. The research design used is pretest and posttest which is guided by the research instrument. The results of the research show that research on the influence of the Cooperative Integrated Reading and Composition learning model on students' social literacy based on the activities carried out by students is in the very good category. This analysis data is obtained from student learning results before and after the test. Apart from that, Normality test analysis, Homogeneity test, and continued with sample T-test were also carried out. The average score obtained when carrying out the pretest for each group of students in class IV A as a whole was 69.75 and in class IV B as a whole was 64.2. After implementation, it was discovered that the average posttest score on social literacy for class IV A students using the CIRC model as a whole was 81.15. And in class IV B using the conventional model the overall score was 76.75. So the conclusion is that the learning outcomes in experimental class IV A were higher than those in control class IV B.